Relationships Between Convexificators and Greenberg–Pierskalla Subdifferentials for Quasiconvex Functions. (2nd December 2017) - Kabgani, Alireza; Soleimani-damaneh, Majid
ABSTRACT: In this paper, the relationship between convexificators and Greenberg–Pierskalla-based (GP-based) subdifferentials for quasiconvex functions is proved. The established results lead to a mean value theorem, a chain rule, and the closedness property for GP-based subdifferentials. Furthermore, the connection between Clarke generalized gradient and Mordukhovich subdifferential with GP-based subdifferentials is highlighted.